What does translation know?. Issue 2 (23rd February 2017) - Andrews, Kimberly Quiogue
ABSTRACT: This essay introduces Christian Hawkey's Ventrakl (2010) into the tradition of 'experimental translation' – translations that deliberately and severely depart from their source texts, opening up the question of what counts as a translation in the first place. I argue that Ventrakl, which stages a long encounter and 'collaboration' with the early twentieth-century Austrian poet Georg Trakl, enriches our understanding of the relationship between translation and contemporary experimental poetic practice through a method that I term 'radical contextualization'. By strenuously foregrounding the processes of learning and composition that go into its vanguardist attempt at an encounter with history, Ventrakl also foregrounds the question of the ethics of learning, particularly as it affects the relationship between artistic originality and historical reliance on pre-codified modes of communication and authority. I read Ventrakl in light of both translation theory (especially the possibilities opened up by Benjamin's famous formulations in 'Die Aufgabe des Übersetzers') and theories of vanguardism and political efficacy in order to point out how important a poetics of translation, particularly one combined with the demystifying properties of contextualisation, can be for a more generalised theory of avant-garde poetic practice.